Study of a Novel Gene Overexpressed in Head & Neck Tumors - A Seghatoleslam; B Wasylyk (Tehran University of Medical Sciences, 2005)
The original sequence of an overexpressed clone from the Differential Display experiment (previously done in the lab) was analysed in NCBI database and comprises the 3' terminus of a novel gene containing two hypothetical ubiquitin conjugating enzyme domain. To identify this novel gene some experiments were performed in vivo. Phenotypical analysis: RT PCR analysis of RNA samples from head & neck tumors showed that the transcript is over-expressed in 11 out of 14 samples (almost 78%). Immunocytochemistry experiments showed that the protein is localized in both the cytoplasm and the nucleus. This data were confirmed by confocal microscopy. Immunohistochemistry on HNSCC samples showed specific signal in tumor versus normal and control. The same expression pattern was observed by in situ hibridization. Functional analysis: 22 Different head and neck cell lines were checked for the expression of this gene at the RNA level and high/ low expressing cell line were selected to use in transfection experiments, in order to begin to understand which pathway(s) are disrupted in the HNSCC tumor, and the basis for the requirement for upregulation and downregulation of this protein. Initial results showed that overexpression inhibits clonogenicity and the rate of growth. FACS analysis of RPMI cells showed a G1 arrest in the cells transiently transfected with a plasmid that expresses the protein compared to control. These cells also were used to establish Stable transfectants. Mass spectrometry analysis of the purified flagged- protein showed some extra bands which could be considered as interacting partner and/or potential substrate for this putative E2 protein. Perspective: functional analysis of this gene including the study of the interactions such as ubiquitination between endogenous protein and its potential partner will be continued to explore the function and the potential role of this gene in cancer.